HUBUNGAN FOOD AND BEVERAGE PRODUCT DAN ORDER TAKER DALAM MENGATASI SOLD OUT DI GRAN PURI HOTEL MANADO - Jeskrispen Lagarense; Sony Wijanarko; Aurelia Manongko (Jurnal Hospitaliti, 2025)
This study aims to analyze and describe the contributing factors leading to sold-out situations, as well as to explore the nature of the working relationship between the Food & Beverage Product division and the Order Taker in addressing such occurrences at Gran Puri Hotel Manado. The research investigates how the Food & Beverage Product division manages the procurement of food ingredients used to serve both guests and staff. This division plays a crucial role not only in the ordering process but also in preventing and resolving sold-out conditions. The findings reveal several factors that contribute to sold-out incidents, particularly within the Room Service Section, where these issues arise due to depleted food stock and the unavailability of ingredients from suppliers or in the market. The role of the Order Taker—as a communication bridge between guests and the Food & Beverage Product division and is vital in mitigating these issues. A professional collaborative relationship is maintained through the timely, accurate, and precise exchange of sold-out data and adherence to the handling procedures established by the Food & Beverage Product team. Effective cooperation with this division is expected to minimize sold-out incidents and ensure full menu availability. Furthermore, the Front Office Department is required to provide accurate guest count information to the Food & Beverage Product division to facilitate adequate food preparation. Keywords: Order Taker, Sold Out, Food & Beverage Product, Room Service